World Bank and compensatory education policy in the State of Acre (Research, Society and Development, 2022)
The article discusses the influence of the World Bank in the design and implementation of the Wings of Forestry Program as a public policy with compensatory function in the State of Acre (2005-2018). This is a qualitative, exploratory study, developed based on the methodological procedures of narrative bibliographic review and documentary research, through the reading of scientific articles, books, national legislation and documents of international organizations contained in official websites. For the analysis and discussion of the results the assumptions of content analysis were considered. The study presents the theoretical basis about compensatory policies. It then presents a brief history of World Bank agendas and their influence on public education policies. Afterwards, it presents and discusses the historical, social and political context under which the Wings of Florestania Program was implemented. The final considerations point to some reflections that endorse the discussions about the Wings of Florestania Program, based on the political models of the State expressed in the policies of the government of Acre, arising from World Bank guidelines. The results indicate that the Wings of Florestania Program brings together elements of the managerialist state model and the minimal state, under the technical/operational influence of the World Bank.